Transformation of the Views of China on the Problem of Supply Chain Management of Territorial Regulation of the Borders of India in the Last Quarter of the XX Century - Vlada Vadimovna Paramonova; Rustem Ravilevich Muhametzyanov; Vitaly Anatolievich Epshteyn (International Journal of Supply Chain Management, 2019)
After the death of Mao Zedong in September 1976, the PRC opens a new page in its foreign policy history. This is mostly due to the reforms and transformations that Deng Xiaoping proclaimed. The change of sociopolitical and economic structures that had taken place laid the foundation for Chinaâ€™s entry into world leaders in some positions. By the time Deng Xiaoping came to power, the Chinese economy was in decline after the â€œpolitical adventuresâ€ of Mao Zedong. To get out of this situation, it was necessary to liberalize the economic and social sectors, as well as solve a whole range of foreign policy problems (from establishing official diplomatic relations with the USA and improving relations with the USSR, to solving the problems of Hong Kong and Macao) in order to become a harmonious part of the world community. To strengthen its position in the Asia-Pacific region, China needed, first of all, to establish relations with all its neighbours and resolve territorial disputes, of which there were many. This article is supposed to consider the question of the attempts of the PRC to resolve existing differences on the disputed parts of the borders with the Republic of India. In the period under review, China had several territorial disputes with its neighbours, which did not allow to realize the foreign policy potential, and there was also not a sufficient number of allies and economic partners of the PRC. As an example of a solution to border disputes, one can cite a positive result achieved in the course of negotiations with the USSR on the demarcation of the border. If China managed to achieve its goals with its northern neighbor, the question with India still remains open.In our study, an attempt will be made to analyse the course of the negotiation process between the PRC and the Republic of India in the last quarter of the 20th century and to identify the reasons for the lack of a decision on this issue. This analysis is interesting not only in terms of forecasting the development of the situation in the APR but also within the framework of other territorial problems of the PRC.